Otonomi Daerah Dalam Masyarakat Multikultural - Supriyono, Bambang (Jurnal Konstitusi & Demokrasi, 2022)
The local government system implemented in a multicultural society, especially in Indonesia, still faces a dilemma. When the government system prioritizes democratic values, there is a tendency to ignore managerial values. Observing these issues, the decentralization policy as the basis for regional autonomy will be appropriately implemented if it considers the balance between diversity and the dimensions of unity or diversity. Understanding these multicultural dimensions needs to be the basis for building relationships between the central and regional governments in administering a government system that truly means local self-governance.